Clustering Shoppers By Mall Experience For Emerging Indian City - Prashar, Sanjeev; Gupta, Sumeet; Singh, Harvinder; T. Sai Vijay , T. Sai Vijay; Parsad, Chandan (Asian Academy of Management (AAM), 2016)
India is undergoing drastic transformation in its organised retail sector. Followed by Tier 1 cities, Tier 2 cities are also witnessing an upsurge in retail malls, owing to the burgeoning middle class, growing income levels and a more accommodative attitude towards modern shopping formats. However, due to increased competition and relatively lower population in these cities, the malls are ending up eating each other's footfalls. Therefore, it is highly imperative for mall managers to ascertain features that would diﬀerentiate them from their competitors. The objective of this study is to segment and profle shoppers based on their orientation towards diﬀerent factors associated with an organised retail using hierarchical and non-hierarchical clustering techniques. Two segments were identifed through the analysis. Each segment was profled in terms of mall attractiveness characteristics, demographics and behavioural factors. Results of both hierarchical and k-means cluster analysis suggests two prominent groups among shoppers, namely relatively higher aged service class people and young students. Constituents of these segments also reveal distinct patterns. The younger segment pays more importance to variables like mall events and promotional schemes being organised by malls and/ or retailers. There is less impact of these variables on aged service class segment. This study is a useful contribution to the existing body of knowledge on management of shopping malls in India and is unique in terms of its focus on consumers' in tier two Indian cities like Raipur. This enables retail managers to prepare suitable retailing policies and strategies to cater to each segment.